(untitled) (ESMAT Magazine, 2019)
It’s undeniable that the criminal law takes new paths, as its internalization has been making important changes in the background of its classical institutes. The direct demand towards people in facing the problem related to the economical delinquency, typical in risk society, offers the possibility for the discussion about if there is place, or not, the company´s criminal liability. Although the Constitution prescribes the personal liability as a tenet, it´s not hard to realize the sprawl of the thoughts that have the tendency to relativize this tenet,which leads to the mistaken imputation of the corporation´s juridical criminal responsability, in the entrepreneurial criminality.For the development of the present work will be used, therefore, as method of approach the dialectical method, through the bibliographical contribution, seeking to identify in the process of knowledge construction the conflicts and contradictions existing in this theme.